The Impact of Compulsory Arbitration on Bargaining Behavior: An Experimental Study - Alexander S. Kritikos (European University Viadrina, Department of Business Administration and Economics, 2005)
A series of experiments compares bargaining behavior under three different settings: no arbitration, conventional and final offer arbitration. Under no arbitration disputes with zero payoffs were around 10%, while the pie was equally split in less than half of the cases. Under conventional arbitration - where the arbitrator is free in choosing his award - every third negotiation ended in dispute giving evidence for a modified chilling effect. Under final offer arbitration - where the arbitrator has to award to the bargainers either one of their final offers - there was only a small increase of disputes while equal splits have doubled to 80%. The experiment shows final offer arbitration, though having lower dispute rates, to interfer more with bargaining behavior than conventional arbitration where the bargaining behavior was similar to the no-arbitration treatment. Under final offer arbitration, negotiators adjust their bargaining strategy to the arbitrator's expected award.
Keywords: C91; D63; C78; 330; Bargaining; Arbitration; Experiments; Fair Awards; Verhandlungstheorie; Schiedsgerichtsbarkeit; Experiment; Theorie